1991
DOI: 10.1002/1097-0142(19911115)68:10<2109::aid-cncr2820681004>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy consisting of cisplatin and continuous infusions of bleomycin and 5-fluorouracil for advanced head and neck cancer. The need for a new stratification for stage IV (MO) disease

Abstract: A Phase II study of cisplatin (100 mg/m2 on day 1 and bleomycin (15 mg intravenous push day 1) followed by 5 days of continuous intravenous infusions of 5‐fluorouracil (5‐FU) (650 mg/m2/d) and bleomycin (16 mg/m2/d) repeated at 21‐day intervals was performed in 54 previously untreated patients with nonmetastatic (MO), locoregionally advanced head and neck squamous cell carcinoma (SCC). The aim of this study was to increase the complete response rate to chemotherapy and to identify prognostic factors that may i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In treating patients with advanced head and neck cancer, there has been a recent trend away from surgery towards chemotherapy and/or radiotherapy thereby improving tumour response rates and disease control whilst attempting to achieve organ preservation. [6][7][8][9][10][11][12] Ahmed et al 6 used concomitant chemoradiotherapy and surgical salvage for N3 nodal disease. Intra-arterial cisplatin and radiotherapy was given with surgical salvage for patients with N3 nodal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In treating patients with advanced head and neck cancer, there has been a recent trend away from surgery towards chemotherapy and/or radiotherapy thereby improving tumour response rates and disease control whilst attempting to achieve organ preservation. [6][7][8][9][10][11][12] Ahmed et al 6 used concomitant chemoradiotherapy and surgical salvage for N3 nodal disease. Intra-arterial cisplatin and radiotherapy was given with surgical salvage for patients with N3 nodal disease.…”
Section: Discussionmentioning
confidence: 99%
“…From these studies, it has been suggested that large volume lymph node metastasis is unlikely to be cured by radiotherapy or by chemoradiotherapy alone. 8,9 Given these results, it is uncertain how this group of patients should be managed and whether aggressive surgery still has arole. Results for neck recurrence in advanced neck disease have been controversial in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Recondo et al 26 investigated the effects of treating advanced head and neck cancer patients with neoadjuvant cisplatin, continuous intravenous bleomycin, and 5‐FU. An overall response rate of 43% was reported for patients with N2C‐N3 disease, and the 3‐year survival was reported to be below 15%.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, from 1987 (third edition), nodal status was measured as nodal size instead of fixation or mobility. Secondly, until 1997, stages I, II, and III defined a limited number of categories, whereas stage IV comprised multiple categories from T4N0M0 to T4N3M1, which led to a very limited prognostic value of the UICC group staging system 12, 13. In attempts to achieve a higher level of discrimination among categories than in the UICC stage classification, various models using the same T and N data have been described 3,10,12,14–16.…”
Section: Introductionmentioning
confidence: 99%